Stem‐cell‐based therapies for retinal degenerative diseases: Current challenges in the establishment of new treatment strategies - Uyama, Hirofumi (Dev Growth Differ, 2021)
Various advances have been made in the treatment of retinal diseases, including new treatment strategies and innovations in surgical devices. However, the treatment of degenerative retinal diseases, such as retinitis pigmentosa (RP) and age‐related macular degeneration (AMD), continues to pose a significant challenge. In this review, we focus on the use of embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) to treat retinal diseases by harnessing the ability of stem cells to differentiate into different body tissues. The retina is a tissue specialized for light sensing, and its degradation leads to vision loss. As part of the central nervous system, the retina has very low regenerative capability, and therefore, treatment options are limited once it degenerates. Nevertheless, innovations in methods to induce the generation of retinal cells and tissues from ESCs/iPSCs enable the development of novel approaches for these irreversible diseases. Here we review some historical background and current clinical trials involving the use of stem‐cell‐derived retinal pigment epithelial cells for AMD treatment and stem cell‐derived retinal cells/tissues for RP therapy. Finally, we discuss our future vision of regenerative treatment for retinal diseases with a partial focus on our studies and introduce other interesting approaches for restoring vision.